Population Dynamics and Seasonal Abundance of some Forest Insect Pests (Nursery Stage) through Light Trap - Meshram, P. B.; Pathak, S. C., Jamaluddin (Indian Forester, 1990)
Population dynamics and seasonal abundance of forest nursery pests through light trap unit was started at State Forest Research Institute Nursery, Jabalpur with the installation of Pennsylvanian light trap unit equipped with 160 W mercury vapour lamp. Results of two years data of 10 adult insect pests in trap catches during 1984-86 seasons are discussed The light trap method is very suitable for surveillance, pest forecasting, ecology, monitoring and management of the pest population in forest nursery.